Students’ Ability in Translating Narrative Text FromBahasa Indonesia Into English in The Fifth Semester at The English Education Study Program of Universitas Bengkulu - Umi Rosyidah; Zahrida Zahrida; Gita Mutiara Hati (Journal of English Education and Teaching, 2020)
The objective of this research is to find out the students’ ability and the students’ problem in translating narrative text from Bahasa Indonesia into English in the fifth semester at the English education program of Universitas Bengkulu. This research was descriptive quantitative approach. The population of the research  was the students’ from the fifth semester of English education study program. The samples were 49 students. The data of this research were collected by using test and interview.The data analysis was done by using Waddington range for students’ translation score table (2001).  The result of the research showed that, the percentage of students’ ability in translating narrative text from Bahasa Indonesia into English was 61.22 % in level 3. It means that more than half of the sampels were in adequate level. Based on the interview the students’ problem in translating narrative text from Bahasa Indonesia into English was mostly in lexical and grammatical. Overall, the fifth semester students of English education study program of Universitas Bengkulu were able to translate the narrative text from Bahasa Indonesia into English